2010
DOI: 10.17221/27/2009-pps
|View full text |Cite
|
Sign up to set email alerts
|

Biological efficacy of some biorational and conventional insecticides in the control of different stages of the Colorado potato beetle, Leptinotarsa decemlineata (Say) (Coleoptera: Chrysomelidae)

Abstract: Osman M. A.M. (2010): Biological efficacy of some biorational and conventional insecticides in the control of different stages of the Colorado potato beetle, Leptinotarsa decemlineata (Say) (Coleoptera: Chrysomelidae). Plant Protect. Sci., 46: 123-134.The biological efficacy of some biorational and conventional insecticides against different stages of Colorado potato beetle, Leptinotarsa decemlineata (Say) (Coleoptera: Chrysomelidae) was evaluated under laboratory and semi-field conditions. Seven different com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
2
4
0
Order By: Relevance
“…Neem extract products inhibited feeding of adult and larval CPB in laboratory studies [ 105 , 106 , 107 ] but are generally slower to bring about control in the field. Compared to our results, other field studies reported similar control effectiveness with Entrust (>95% control) and Azera (68% to 77% control) [ 103 , 108 , 109 , 110 , 111 ]. Nault and Seaman [ 108 ] also found no significant difference in control between low and high application rates of Entrust.…”
Section: Resultssupporting
confidence: 79%
“…Neem extract products inhibited feeding of adult and larval CPB in laboratory studies [ 105 , 106 , 107 ] but are generally slower to bring about control in the field. Compared to our results, other field studies reported similar control effectiveness with Entrust (>95% control) and Azera (68% to 77% control) [ 103 , 108 , 109 , 110 , 111 ]. Nault and Seaman [ 108 ] also found no significant difference in control between low and high application rates of Entrust.…”
Section: Resultssupporting
confidence: 79%
“…Experiments revealed that a temperature of 15 • C with a concentration of 0.2% in combination caused significantly higher mortality of adult insects than other temperatures and concentrations [17]. Similar positive effects were experienced in other laboratory and field experiments for spinosad and combinations with other ecological insecticides [96][97][98]. In addition to spinosad, the mixture of avermectin B1 (80%) and avermectin B1b (29%), and avermectin C also reached strong efficacy against third instar larvae and adults [96].…”
Section: Environmentally Friendly Insecticides Synergists and Their C...supporting
confidence: 70%
“…Concerning combinations with spinosad, mixtures with Btt, azadirachtinand pyrethrin proved to be very active in both laboratory and field studies (Barčić et al, 2006). Furthermore, the efficacy of low doses of spinosad, Btt, and azadirachtin has been detected and the effect of combinations for these three alternative insecticides has been proposed [97].…”
Section: Environmentally Friendly Insecticides Synergists and Their C...mentioning
confidence: 99%
“…Similarly, the insecticide is applied to control the thrips Frankliniella spp. in horticultural and ornamental crops40 and Leptinotarsa decemlineata L. in potatoes 41. Furthermore, even though it has not yet been registered worldwide, spinosad is active against several stored‐grain pests 42, 43…”
Section: The Spinosad: History and Current Use Worldwidementioning
confidence: 99%
“…in horticultural and ornamental crops 40 and Leptinotarsa decemlineata L. in potatoes. 41 Furthermore, even though it has not yet been registered worldwide, spinosad is active against several stored-grain pests. 42,43 After spinosyn introduction, spinosad resistance events were documented for some insects, such as houseflies and fruit flies, Lepidoptera and thrips species.…”
Section: The Spinosad: History and Current Use Worldwidementioning
confidence: 99%